2011
DOI: 10.18848/2156-8960/cgp/v01i03/41178
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Gardens in Maycoba, Mexico: Change in the Environment of a Population Genetically Prone to Diabetes

Abstract: Gardens are an important part of the environment as they play multiple roles and are central to the lifestyle and economy of many communities. The investigators use qualitative methods to explore patterns and perceptions about changes in gardening and cultivation in the community of Maycoba, Mexico. Maycoba is home to a large community of Pima Indians, an Indigenous population genetically prone to diabetes. Pima Indians living in the United States have been shown to have an extremely high prevalence of diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Specific assessments of environmental change in Maycoba over the 15-year time span have been previously described and included aspects of the changing food environment ( 9 , 11 ) and changes in land use and land cover ( 10 ). Chaudhari et al ( 11 ) found the food environment, with regard to food availability and food acquisition behaviors, had transitioned from a subsistence-based diet with very limited processed food items to one that incorporates more purchased foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific assessments of environmental change in Maycoba over the 15-year time span have been previously described and included aspects of the changing food environment ( 9 , 11 ) and changes in land use and land cover ( 10 ). Chaudhari et al ( 11 ) found the food environment, with regard to food availability and food acquisition behaviors, had transitioned from a subsistence-based diet with very limited processed food items to one that incorporates more purchased foods.…”
Section: Discussionmentioning
confidence: 99%
“…Over the ensuing 15 years, the community of Maycoba experienced marked changes in the socioeconomic and built environment, including the introduction of paved roads, piped drinking water, electricity, retail food, clothing, and hotel establishments; changes in land usage; and increased transportation options ( 9 – 11 ). In 2010, another survey was undertaken in Maycoba to examine the impact of these environmental changes on the prevalence of type 2 diabetes and obesity ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of increase in MSNA with increasing adiposity and insulinemia in Pima Indians may explain, in part, why this population has a low tendency for hypertension despite the high prevalence of obesity and hyperinsulinemia. The Pima Indians living in Mexico, carrying the same genotype, but who enjoy a more modest environment, have a much less dramatic phenotype [84]. Similarly to Pima Indians, a cross-sectional analysis of 27 808 adults aged 45-73 years participating in the Malmö Diet and Cancer study showed that obesity was 40% more prevalent in non-Swedish Europeans compared with Swedes [85].…”
Section: Genetic and Ethnic Differences Modify The Association Of Obementioning
confidence: 99%
“…The role of family gardens was examined with regard to their impact on food consumption and physical labor [30]. Qualitative methods--interviews, two focus groups, and a household survey--were employed to explore changes in gardening and cultivation practices over the fifteen-year span between the two studies.…”
Section: Environmental Changementioning
confidence: 99%
“…These findings suggested that change has occurred, but not as dramatic as originally presumed. The physical activity linked to cultivation may continue as an important factor in weight control and thereby, the prevention of diabetes [30]. …”
Section: Environmental Changementioning
confidence: 99%